Under-Consumption Penalties in the Low Carbon Market: Reflections From a Spanish Social Housing Provider - Antepara, Iñigo (Frontiers in Sustainable Cities, 2021)
This proposal focuses on the analysis of three case studies of a Spanish social landlord – Basque Alokabide, submitted to the Carbon Fund for a Sustainable Economy. The calculation of CO2 emissions follows the methodology recommended by the Spanish government. The economic viability of the cases analyzed is calculated, first without taking into account the money obtained from the carbon market, and then taking advantage of the sale of the emissions. The interest value of this work is the examination of how low incomes tend to be overrepresented in social housing, resulting in lower energy consumption and colder dwellings. Since low income tenants under-consume energy, before renovation CO2 emissions are lower, and therefore Alokabide is taking less advantage of the carbon market. Additionally, photovoltaic systems, while easier to implement even at district level, are not eligible in the Spanish program, and this is also disadvantageous. In the policy recommendations, the ex-ante accounting of emissions should be justified on the basis of theoretical energy consumption with average consumers, rather than verifying ex-post actual emissions by low income household that under consume: energy efficiency measures lead to improved thermal comfort, and this added benefit should be taken into account in the economic viability. Towards the goal of reducing emissions after retrofitting, decarbonization is more feasible than the reduction of the energy consumption through the substitution of fossil fuels by renewables to satisfy primary energy needs.